(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
In this article, the institution of impunity concept, history of origin, legal significance,an idea about the types and scope of application is conducted. It is also developed in research work exempt from punishment under the laws of foreign countries specific aspects of doing and milits issues of implementation of our legislation illuminated